Reference library of American men /Vol II - Mossman, Jennifer (Farmington Hills, MI : Gale Research : Distributed exclusively by African American Publications, 2002)
A comprehensive source for biographical information on 650 men who have gained international recognition for their enduring contributions to human culture and society.
v. 1. A-D -- v. 2. E-J -- v. 3. K-P -- v. 4 O-Z.
Includes bibliographical references and indexes.
85591
Keywords: Men -- United States -- Biography -- Dictionaries; Men -- Biography -- Dictionaries